Phosphorylation of the Mdm2 oncoprotein by the c-Abl tyrosine kinase regulates p53 tumor suppression and the radiosensitivity of mice - Carr, Michael I.; Roderick, Justine E.; Zhang, Hong; Woda, Bruce A.; Kelliher, Michelle A.; Jones, Stephen N. (Proceedings of the National Academy of Sciences - PNAS, 2016)
The p53 tumor suppressor acts as a guardian of the genome by preventing the propagation of DNA damage-induced breaks and mutations to subsequent generations of cells. We have previously shown that phosphorylation of the Mdm2 oncoprotein at Ser394 by the ATM kinase is required for robust p53 stabilization and activation in cells treated with ionizing radiation, and that loss of Mdm2 Ser394 phosphorylation leads to spontaneous tumorigenesis and radioresistance in Mdm2S394A mice. Previous in vitro data indicate that the c-Abl kinase phosphorylates Mdm2 at the neighboring residue (Tyr393) in response to DNA damage to regulate p53-dependent apoptosis. In this present study, we have generated an Mdm2 mutant mouse (Mdm2Y393F ) to determine whether c-Abl phosphorylation of Mdm2 regulates the p53-mediated DNA damage response or p53 tumor suppression in vivo. The Mdm2Y393F mice develop accelerated spontaneous and oncogene-induced tumors, yet display no defects in p53 stabilization and activity following acute genotoxic stress. Although apoptosis is unaltered in these mice, they recover more rapidly from radiation-induced bone marrow ablation and are more resistant to whole-body radiation-induced lethality. These data reveal an in vivo role for c-Abl phosphorylation of Mdm2 in regulation of p53 tumor suppression and bone marrow failure. However, c-Abl phosphorylation of Mdm2 Tyr393 appears to play a lesser role in governing Mdm2-p53 signaling than ATM phosphorylation of Mdm2 Ser394. Furthermore, the effects of these phosphorylation events on p53 regulation are not additive, as Mdm2Y393F/S394A mice and Mdm2S394A mice display similar phenotypes.